2018
DOI: 10.1038/s41598-018-20320-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Role of Ca2+ and Hard Divalent Metal Cations on Accelerated Fibrillation and Interfibrillar Aggregation of α-Synuclein

Abstract: α-Synuclein (αSyn) is an intrinsically disordered protein, the aggregation of which is highly related to the pathology of diverse α-synucleinopathies. Various hard divalent metal cations have been shown to affect αSyn aggregation. Especially, Ca2+ is suggested to be a crucial ion due to its physiological relevance to α-synucleinopathies. However, the molecular origin of αSyn aggregation mediated by the metal ions is not fully elucidated. In this study, we revealed that hard divalent metal ions had almost ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 52 publications
4
40
0
Order By: Relevance
“…The binding of multiple Ca(II) ions (up to four) to AS (Fig. ) has been demonstrated using multiple biophysical methods, including ion mobility‐mass spectrometry (IM‐MS), synchrotron small‐angle X‐ray scattering and transmission electron microscopy in combination with molecular dynamics (MD) (Han et al ). As observed with other divalent metal ions, Ca(II) was shown to induce a structural transition of AS monomers to extended conformations, promoting the exposure of the NAC region and rapid AS fibrillation.…”
Section: α‐Synuclein Is a Metal‐binding Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding of multiple Ca(II) ions (up to four) to AS (Fig. ) has been demonstrated using multiple biophysical methods, including ion mobility‐mass spectrometry (IM‐MS), synchrotron small‐angle X‐ray scattering and transmission electron microscopy in combination with molecular dynamics (MD) (Han et al ). As observed with other divalent metal ions, Ca(II) was shown to induce a structural transition of AS monomers to extended conformations, promoting the exposure of the NAC region and rapid AS fibrillation.…”
Section: α‐Synuclein Is a Metal‐binding Proteinmentioning
confidence: 99%
“…The study concluded that Ca(II) ions also trigger non‐specific inter‐fibrillar aggregation via electrostatic and hydrophobic interactions to produce large AS aggregates (Fig. c) (Han et al ). Several studies have demonstrated that Ca(II) binds to AS through the C‐terminal region (Lowe et al ; de Laureto et al ); and it interferes with normal AS‐membrane interactions.…”
Section: α‐Synuclein Is a Metal‐binding Proteinmentioning
confidence: 99%
“…The familial PD mutations have been shown to alter alpha-synuclein oligomerisation and subsequent aggregation (Winner et al, 2011), demonstrating a probable role for alpha-synuclein misfolding and aggregation in PD. Ligand binding has also been demonstrated to effect alpha-synuclein aggregation, with binding of some compounds such as divalent metal cations (Han, Choi and Kim, 2018) and biological polyamines (Krasnoslobodtsev et al, 2012) increasing aggregation, and others such as squalamine (Perni et al, 2017) and curcumin (Herva et al, 2014) decreasing aggregation.…”
Section: Alpha-synuclein Aggregationmentioning
confidence: 99%
“…The binding of many other small molecules has been investigated using IMS-MS, including investigations into spermine (Grabenauer et al, 2008), calcium (Han, Choi and Kim, 2018), dopamine (Illes-Toth, Dalton and Smith, 2013), epigallocatechin gallate (EGCG) (Konijnenberg et al, 2016) and gallic acid (Liu et al, 2014). A common finding of these studies was an increase in compact conformations upon binding of compounds known to increase alpha-synuclein aggregation, such as spermine (Grabenauer et al, 2008), and prevention of the formation of compact conformations by compounds which inhibit aggregation, such as gallic acid (Liu et al, 2014).…”
Section: Ligand Bindingmentioning
confidence: 99%
See 1 more Smart Citation